2011
DOI: 10.1002/adma.201101460
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Lattice Thermal Conductivity in Single Bi‐Te Core/Shell Nanowires with Rough Interface

Abstract: The role of the interface roughness of Bi‐Te core/shell nanowires is reported in reducing lattice thermal conductivity, which are prepared by on‐film formation of nanowire (OFF‐ON) that is capable of growing high‐quality single‐crystalline Bi nanowires, and by the subsequent sputtering of Te onto the Bi nanowires. The rough interface Bi‐Te core/shell nanowires exhibit lower thermal conductivities than that of smooth interface counterparts, while electrical conductivities for these two types of nanowires are si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
83
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 25 publications
5
83
0
Order By: Relevance
“…4c). The recent experimental study by Kang et al [30] has found that the interface roughness of core-shell nanowires can be engineered in experiment by applying different deposition power, with high power resulting in the rough interface. Moreover, their experimental study has reported the reduction of thermal conductivity in Bi/Te core-shell nanowires with rough interface, which is consistent with our results that interface roughness leads to further reduction of thermal conductivity in core-shell nanowires.…”
mentioning
confidence: 99%
“…4c). The recent experimental study by Kang et al [30] has found that the interface roughness of core-shell nanowires can be engineered in experiment by applying different deposition power, with high power resulting in the rough interface. Moreover, their experimental study has reported the reduction of thermal conductivity in Bi/Te core-shell nanowires with rough interface, which is consistent with our results that interface roughness leads to further reduction of thermal conductivity in core-shell nanowires.…”
mentioning
confidence: 99%
“…Nano-heterostructures may exhibit a low thermal conductivity due to interface phonon scattering [41]. A core-shell structure is another effective method for reducing the thermal conductivity where the rough interface acts as a secondary scattering phase.…”
Section: S T Ztmentioning
confidence: 99%
“…A core-shell structure is another effective method for reducing the thermal conductivity where the rough interface acts as a secondary scattering phase. Kang et al [41] reported the possibility to reduce the thermal conductivity of Bi/Te core-shell nanowires to an amount close to the amorphous limit. While the electrical conductivity of the core/shell nanowires does not change appreciably, their thermal conductivity can be five times lower than the conventional nanowire of the same size.…”
Section: S T Ztmentioning
confidence: 99%
“…Recently, Kim et al reported that ferric benzenesulfonate (Fe(Bzs) 3 ) is a better oxidant for achieving higher electrical conductivity in the 3,4-ethylenedioxythiophene (EDOT) polymerization process than the generally used oxidant, ferric paramethylbenzenesulfonate (Fe(p-MeBzs) 3 ).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have mainly involved relatively high efficient inorganic TE materials, including semiconductors such as Bi 2 Te 3 , Bi-Te alloys, CoSb 3 , SiGe, and MgSi, conducting oxides such as NaCo 2 O 4 and CaMnO 3 , and metal alloys such as BiSb. [1][2][3] However, high cost of the raw materials, potential for heavy metal pollution, and processing difficulties limit widespread practical applications of these materials. In this regard, recent studies have focused on TE composites consisting of an inorganic conductive filler and an organic polymer matrix, which have become promising alternatives to inorganic TE materials.…”
Section: Introductionmentioning
confidence: 99%